(untitled) (Human Factors in Design, 2024)
The communication rehabilitation process in autistic children requires support tools for physiotherapy and speech therapy sessions, the so-called assistive technologies. One of these tools is rehabilitation apps. However, the applications most used for this purpose can present a complex interface. Therefore, existing applications were analyzed, and two applications were selected (Let me talk and Symbo Talk), because they are widespread in the rehabilitation segment and because they have a greater number of functionalities. To analyze the usability of these applications, usability tests were carried out by task, with seven volunteer specialists, who work at the Centro Catarinense de Reabilitação (CCR) in Florianópolis. As a result, the Let me talk App was rated highest for its usability.